Investigation of Uses of Purple and Orange Sweet Potato Dietary Fiber Concentrates in Sucuks - Meryem Göksel Saraç; Emre Hastaoğlu; Burak Dinçel; Özlem Pelin Can (Turkish Journal of Agriculture: Food Science and Technology, 2021)
Dietary fibers have positive effects on the product structure thanks to their technological features. The aim of this study is to determine the effect of dietary fibers obtained from purple and orange sweet potato varieties on heat-treated sucuks. For this purpose, dietary fibers were produced from sweet potato varieties and their characterizations were determined. Then, sweet potato fibers were added to the sucuks in the amount included in their formulation and the effects of dietary fiber change were examined in terms of physicochemical, bioactive, textural and sensory. In this context, it was determined that the color change in sweet potatoes affected the color properties of the dietary fibers obtained. In addition, it was observed that the hardness value was the highest (1715.35 g) in sucuks to which orange sweet potato starch, which has high oil and water binding values, and the sweet potato fibers changed the product properties compared to the control group. Total phenolic content of sucuks was determined in the range of 60.57-130.45 mg/ml gallic acid and it was determined that sweet potato fibers increased the phenolic content. As a result of the study, it was determined that sweet potato dietary fibers are an alternative additive for sucuks.